Dental Caries Experience in Northern Manhattan Adolescents - Dennis A. Mitchell, DDS, MPH; Kavita P. Ahluwalia, DDS, MPH; David A. Albert, DDS, MPH; (Blackwell Synergy, 2003)
The study sought to document dental caries among adolescents residing in northern Manhattan, New York, by race, sex, and community